EFFICACY OF CHEMICAL CONTROL METHODS AGAINST MAJOR WHEAT PESTS - Alamuratov Rayimjon Abdimurotovich (American Journal Of Agriculture And Horticulture Innovations, 2024)
This article investigates the insecticidal activity of the chemical preparation Antikolorad Max, sus.k., against major wheat pests such as harmful bugs, slimy worms, wheat thrips, and grain aphids. According to the results of the experiment, when this preparation was applied at a rate of 0.1-0.15 l/ha, it demonstrated a biological efficiency of 88.6-92.5% against harmful bugs, 91.6-94.8% against slimy worms, 89.4-95.8% against wheat thrips, and 89.4-93.1% against aphids 14 days after application.